RATE BASE PROBLEMS PRESENTED WHEN UTILITIES SHIFT FROM RETIREMENT TO DEPRECIATION ACCOUNTING. - Krebs, William S. (The Accounting Review, 1950)
Abstract What is properly labeled "retirement accounting" is a doctrine of great importance. According to this doctrine no depreciation charges, as such, are set up annually on the books and no estimate is made of the periodic depreciation accrual. The significant point of time, in the view of its advocates, is the period when the asset is withdrawn from service. At this time the original cost of the asset is charged to operating expenses. Specifically the procedure sets up asset accounts to which the cost of all property purchased or constructed is charged at the time it is acquired. These charges remain on the books until property is abandoned and then the original cost of the asset is charged to operating expenses. In effect an account like "Retirement Expense" is charged when an asset account is credited for the amount of the original cost of the asset abandoned. The scrap value realized, if the asset is sold, is charged to cash and credited to "Retirement Expense." Or if the asset is "junked" in place of being sold, the charge is made to materials and supplies account and the credit to "Retirement Expense" account for the amount of the appraised value of the asset.